2017
DOI: 10.1177/1010428317701654
|View full text |Cite
|
Sign up to set email alerts
|

Forced expression of Wnt antagonists sFRP1 and WIF1 sensitizes chronic myeloid leukemia cells to tyrosine kinase inhibitors

Abstract: Chronic myeloid leukemia is a clonal myeloproliferative disorder that arises from the neoplastic transformation of the hematopoietic stem cell, in which the Wnt/β-catenin signaling pathway has been demonstrated to play an important role in disease progression. However, the role of Wnt signaling antagonists in therapy resistance and disease progression has not been fully investigated. We aimed to study the effects of Wnt/β-catenin pathway antagonists-secreted frizzledrelated protein 1 and Wnt inhibitory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, CML patients with methylated SFRP1 correlated with imatinib therapy resistance as well as additional second Philadelphia chromosome abnormalities [93]. Moreover, expression of antagonists SFRP1 and WIF1 was shown to sensitize chronic myeloid leukemia (CML) cells to tyrosine kinase inhibitors [94]. In in vitro experiments involving K562 cells stably expressing SFRP1, the sensitivity toward imatinib, dasatinib, and nilotinib, were 75%, 43%, and 48% more sensitive, respectively, when compared to empty vector-transfected controls [94].…”
Section: Sfrp1 and Chemotherapy Responsementioning
confidence: 99%
“…However, CML patients with methylated SFRP1 correlated with imatinib therapy resistance as well as additional second Philadelphia chromosome abnormalities [93]. Moreover, expression of antagonists SFRP1 and WIF1 was shown to sensitize chronic myeloid leukemia (CML) cells to tyrosine kinase inhibitors [94]. In in vitro experiments involving K562 cells stably expressing SFRP1, the sensitivity toward imatinib, dasatinib, and nilotinib, were 75%, 43%, and 48% more sensitive, respectively, when compared to empty vector-transfected controls [94].…”
Section: Sfrp1 and Chemotherapy Responsementioning
confidence: 99%
“…In healthy cells β-catenin levels are tightly controlled by secreted and/or intracellular located inhibitory proteins. Epigenetic abnormalities and silencing suppressors of the pathway trigger the increase of β-catenin levels, leading to the uncontrolled activation of the Wnt signaling pathway [26,27].…”
Section: Wnt Signaling In Hematological Malignanciesmentioning
confidence: 99%
“…Regarding therapeutic interventions, Pehlivan et al showed that induced WIF1 expression will sensitize CML cells to tyrosine kinase inhibitors, again making Wnt signaling a promising target in TKI resistant patients. The WIF1 gene was reported to be hypermethylated in CML cell lines [27]. However, to date there has been no reports on the expression levels and regulatory effect of WIF1 in CML patients.…”
Section: Wnt Inhibitory Factor 1 (Wif1)mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was reported that Sfrp1 was beneficial in recovering cardiac function and structural damage in animal model of myocardial infarction [ 6 ]. Sfrp1 was proved to compete the frizzled receptor of Wnt signaling and further to act as a suppressor of Wnt signaling [ 7 ].…”
Section: Introductionmentioning
confidence: 99%